Swimming against the current: Negotiating leadership challenges for women in Iran. (February 2022) - Gilani, Parisa; Rook, Caroline; Razeghi, Yasamin; Carr, Melissa
The representation and progression of women in leadership roles is a global issue, but research insights on the enactment of leadership by women stem from a predominantly Western perspective. As leadership is inherently context-dependent, we focus on a specific 'place' of leadership enactment and provide a more situated and contextual understanding of the challenges women in Iran face in entering and enacting leadership roles. This study contributes to the understanding of leadership and place by considering the dynamics of place as occurring at multiple levels – societal norms (including religion), organisational and physical (including geographical). For this in-depth inductive study 24 semi-structured interviews were conducted and analysed through Reflexive Thematic Analysis. Through the intersection of different spheres of place particular challenges for women arise. The women within our study had to negotiate the complex dynamics of doing gender well and being seen to act in line with the normative conceptions of femininity with dominant masculine expectations of what leadership and how it should be done. While also women Western contexts are constrained and / or supported by cultural (national, societal and organisation) factors as well as place in a physical and geographical sense, the specific nuances in national and societal cultural norms and the 'harsh' physical environment in our study provide additional challenges for women to negotiate. This study affords female leaders in Iran a voice and extends previous work on the lived experiences of women in the Middle East and North Africa Region in the under-researched context of Iran.